Contribution of free satellite time-series images to mapping plant communities in the Mediterranean Natura 2000 site: the example of Biguglia Pond in Corse (France) - Rapinel, Sébastien; Rozo, Clémence; Delbosc, Pauline; Bioret, Frédéric; Bouzillé, Jan-Bernard; Hubert-Moy, Laurence (Mediterranean Botany, 2020)
Mapping plant communities, which is essential to assess the conservation status of natural habitats, is currently based mainly on time-consuming field surveys without the use of satellite data. However, free image time-series with high spatial and temporal resolution have been available since 2015. This study assessed the contribution of Sentinel-2 time-series images to mapping the spatial distribution of 18 plant communities within a Natura 2000 site (1978 ha) located on the Mediterranean biogeographical region (Corsica, France). The method was based on random forest modeling of six Sentinel-2 images acquired from 26 February to 24 October 2017, which were calibrated and validated using a field vegetation map. The results showed that the 18 plant communities were modeled correctly, with 72% overall accuracy. The uncertainty map associated with the model indicated areas that required additional field observations.